Factors affecting establishment and population growth of the invasive weed Ambrosia artemisiifolia - Zhao, Wenxuan; Xue, Zhifang; Liu, Tong; Wang, Hanyue; Han, Zhiquan (Frontiers in Plant Science, 2023)
Ambrosia artemisiifolia is a highly invasive weed. Identifying the characteristics and the factors influencing its establishment and population growth may help to identify high invasion risk areas and facilitate monitoring and prevention efforts. Six typical habitats: river banks, forests, road margins, farmlands, grasslands, and wastelands, were selected from the main distribution areas of A. artemisiifolia in the Yili Valley, China. Six propagule quantities of A. artemisiifolia at 1, 5, 10, 20, 50, and 100 seeds m-2 were seeded by aggregation, and dispersion in an area without A. artemisiifolia. Using establishment probability models and Allee effect models, we determined the minimum number of seeds and plants required for the establishment and population growth of A. artemisiifolia, respectively. We also assessed the moisture threshold requirements for establishment and survival, and the influence of native species. The influence of propagule pressure on the establishment of A. artemisiifolia was significant. The minimum number of seeds required varied across habitats, with the lowest being 60 seeds m-2 for road margins and the highest being 398 seeds for forests. The minimum number of plants required for population growth in each habitat was 5 and the largest number was 43 in pasture. The aggregation distribution of A. artemisiifolia resulted in a higher establishment and survival rate. The minimum soil volumetric water content required for establishment was significantly higher than that required for survival. The presence of native dominant species significantly reduced the establishment and survival rate of A. artemisiifolia. A. artemisiifolia has significant habitat selectivity and is more likely to establish successfully in a habitat with aggregated seeding with sufficient water and few native species. Establishment requires many seeds but is less affected by the Allee effect after successful establishment, and only a few plants are needed to ensure reproductive success and population growth in the following year. Monitoring should be increased in high invasion risk habitats.